A framework for identifying the sources of local currency price stability with an empirical application - Pinelopi K. Goldberg; Rebecca Hellerstein (Federal Reserve Bank of New York, 2007)
The inertia of the local-currency prices of traded goods in the face of exchange-rate changes is a well-documented phenomenon in international economics. This paper develops a structural model to identify the sources of this local-currency price stability and applies it to microdata from the beer market. The empirical procedure exploits manufacturers' and retailers' first-order conditions in conjunction with detailed information on the frequency of price adjustments following exchange-rate changes to quantify the relative importance of local nontraded cost components, markup adjustment by manufacturers and retailers, and nominal price rigidities in the incomplete transmission of such changes to prices. We find that, on average, approximately 60 percent of the incomplete exchange rate pass-through is due to local nontraded costs, 8 percent to markup adjustment, 30 percent to the existence of own-brand price adjustment costs, and 1 percent to the indirect/strategic effect of such costs, though these results vary considerably across individual brands according to their market shares.
Keywords: F0; D4; L1; 330; pricing to market; exchange-rate pass-through; markups; nominal rigidities; menu costs; Außenhandelspreis; Wechselkurs; Preisniveaustabilität; Bier; Ökonometrisches Modell; USA